Reference Values and Influencing Factors Analysis for Current Perception Threshold Testing Based on Study of 166 Healthy Chinese - Yin, Hexiang; Liu, Mingsheng; Zhu, Yicheng; Cui, Liying (Frontiers in Neuroscience, 2018)
The current perception threshold (CPT) is a device which can evaluate different sensory fibers quantitatively through different frequencies of the electrical stimulus and has been applied in clinical practice. Previous studies have implied that CPT values may be affected by age, gender, and other factors, yet not conclusively. The objective of our study is to clarify the influencing factors of CPT values and establish a reference value range. Twenty healthy volunteers recruited publicly and 146 subjects who took CPT tests in the census of the national project cardiovascular and cerebrovascular diseases in rural areas of China from 2013 to 2015 were analyzed. Past medical history and demographic characteristics such as age, gender, and occupation were collected. Each subject was tested on the left index finger (or back of the left hand) and the right hallux. CPT values of 2000, 250, and 5 Hz on both sites were recorded for statistical analysis. Gender differences were shown at 2000 Hz CPT on the back of the hand and hallux (p < 0.01), and male subjects had a higher CPT. Age had a positive correlation with 250 Hz CPT on the index finger (p < 0.05, r = 1.5), 2000 Hz CPT on the back of the hand (p < 0.001, r = 1.2) and index finger (p < 0.05, r = 2.5). Manual workers had a higher 250 Hz CPT on the hallux than mental workers (p < 0.01). After investigating the impact of different factors on CPT testing, we established the reference value for subjects with different characteristics.